A Comparison of New Factor Models in the Korean Stock Market. (28th October 2019) - Kang, Hankil; Kang, Jangkoo; Kim, Wooyeon
Abstract: We compare the empirical performance of the Fama and French (2015) five‐factor model, the Hou et al . (2015) q‐factor model, and their variations in the Korean stock market. Among the models considered, we demonstrate that the adjusted five‐factor model, which includes the quarterly‐ rather than the yearly‐based profitability factor, best explains the size‐, value‐, investment‐, and profitability‐sorted portfolio returns. We also document supporting evidence that high‐minus‐low (HML) may not be a redundant factor in the existence of q‐factors. The adjusted five‐factor model outperforms the other factor models in digesting various anomalies in the Korean market.